2015
DOI: 10.1063/1.4934655
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the propagation of pulsed atmospheric plasma streams: From single jet to multi jet arrays

Abstract: Atmospheric pressure plasma propagation inside long dielectric tubes is analyzed for the first time through nonintrusive and nonperturbative time resolved bi-directional electric field (EF) measurements. This study unveils that plasma propagation occurs in a region where longitudinal EF exists ahead the ionization front position usually revealed from plasma emission with ICCD measurement. The ionization front propagation induces the sudden rise of a radial EF component. Both of these EF components have an ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 31 publications
8
139
0
1
Order By: Relevance
“…These values are in agreement with previous computational results [33] which shows that around 70% of the total energy is dissipated by plasma electrons, while most of the remaining energy could be dissipated by plasma ions. Electric field measurements using spectroscopic measurements returns values of around 20 kV/cm along the along the outside plasma jet [34], consistent with the time resolved measurements using Pockels effect based probes [35].…”
Section: Plasma Source Quasi-stationary Working Regimementioning
confidence: 49%
“…These values are in agreement with previous computational results [33] which shows that around 70% of the total energy is dissipated by plasma electrons, while most of the remaining energy could be dissipated by plasma ions. Electric field measurements using spectroscopic measurements returns values of around 20 kV/cm along the along the outside plasma jet [34], consistent with the time resolved measurements using Pockels effect based probes [35].…”
Section: Plasma Source Quasi-stationary Working Regimementioning
confidence: 49%
“…The magnitude of typical electric fields experienced at tissue surfaces was shown to be comparable with field strengths that are known to be biologically important [90]. One of these possible effects is the observation that plasma jets applied to mouse skin induces a significant increase in local blood flow and blood O 2 content [91].…”
Section: Medical Applicationsmentioning
confidence: 76%
“…[15][16][17] In a single plasma jet, the effects of fluid field, electrical field, and device structure on the electrical characteristics, propagation dynamics, and plume length have been widely investigated with optical and electrical diagnosis, ICCD imaging, and Schlieren photography. [18][19][20][21][22][23] It has been found that the plasma plume propagates in different modes, [10,24] there are strongly nonlinear coupling effects of ionization waves determining streamer propagation, [25] the gas heating is the dominant factor for the transition of laminar to turbulent of plasma jet and the plume length, [3,26] and the linear-field and cross-field structures APPJs have also been compared and studied. [27] For jet arrays, there are strong jet-to-jet coupling interactions causing by gas flowing and electrical field from adjacent plasma plumes, which leads to plume divergence, [10,28] different discharge modes, [14,29] and thus affects the downstream plume uniformity and treatment effects.…”
Section: Introductionmentioning
confidence: 99%
“…[27] For jet arrays, there are strong jet-to-jet coupling interactions causing by gas flowing and electrical field from adjacent plasma plumes, which leads to plume divergence, [10,28] different discharge modes, [14,29] and thus affects the downstream plume uniformity and treatment effects. [18,30] To obtain economic, uniform, and large scale APPJ arrays for diverse applications, it is important to understand the mechanisms of the plasma jets interaction and jets propagation of the jet array in the surrounding air. However, most of the reported works on plasma arrays were about the realization of the uniform and large scale plasma area, and only a few of them conducted the experimental measurements and theoretical studies of the plasma jets interactions.…”
Section: Introductionmentioning
confidence: 99%